BALANCED SCORECARD IMPLEMENTATION as a MEASUREMENT of THE UB HOTEL PERFORMANCE ASSESSMENT - Satrio Mangkunegoro; Helmy Adam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Assessment using the Balanced Scorecard (BSC) method is effective and efficient for the UB Hotel at this time. BSC has a distinctive feature because this methods does not only consider the financial perspective to achieve their vision and mission, but also consider other perspectives such as customer perspective, internal business process perspective, and learning and growth perspective. The result of this research object is expected to make evaluation of the hotel easy. Keywords: Balanced scorecard, financial perspective, customer perspective, internal business perspective, learning and growth perspective.